Synthesis and characterization of a highly two-photon active dendrimer derived from 2,3,8-trifunctionalized indenoquinoxaline units - Lin, Tzu-Chau; Liu, Che-Yu; Li, May-Hui; Liu, Yi-You; Tseng, Sheng-Yang; Wang, Yu-Ting; Tseng, Ya-Hsin; Chu, Hui-Hsin; Luo, Chih-Wei (My University, 2014)
A dendritic chromophore derived from 2,3,8-trifunctionalized indenoquinoxaline units was synthesized and experimentally shown to manifest very strong and widely-dispersed two-photon absorption (2PA) across the dynamic tuning range of a Ti:sapphire laser. The maximum 2PA of the studied chromophore was found to reach approximate to 31 700 GM, indicating that 2,3,8-trifuctionalized indenoquinoxaline units are useful building moieties for the construction of highly active 2PA-dyes. In addition, this dendritic structure was also demonstrated to effectively regulate the optical power of femtosecond laser pulses at 800 nm.